A Fairness-Aware Strategy for B5G Physical-Layer Security Leveraging Reconfigurable Intelligent Surfaces - A. Pierron; M. Barbeau; Luca De Cicco; J. Rubio-Hernan; J. Garcia-Alfaro (Foundations and Practice of Security: 18th International Symposium, FPS 2025, Brest, France, November 25–27, 2025, Revised Selected Papers, Part II, 2026)
Reconfigurable Intelligent Surfaces are composed of physical elements that can dynamically alter electromagnetic wave properties to enhance beamforming and lead to improvements in areas with low coverage properties. When combined with Reinforcement Learning techniques, they have the potential to enhance both system behavior and physical-layer security hardening. In addition to security improvements, it is crucial to consider the concept of fair communication. Reconfigurable Intelligent Surfaces must ensure that User Equipment units receive their signals with adequate strength, without other units being deprived of service due to insufficient power. In this paper, we address such a problem. We explore the fairness properties of previous work and propose a novel method that aims at obtaining both an efficient and fair duplex Reconfigurable Intelligent Surface-Reinforcement Learning system for multiple legitimate User Equipment units without reducing the level of achieved physical-layer security hardening. In terms of contributions, we uncover a fairness imbalance of a previous physical-layer security hardening solution, validate our findings and report experimental work via simulation results. We also provide an alternative reward strategy to solve the uncovered problems and release both code and datasets to foster further research in the topics of this paper.
Keywords: B5G; Reconfigurable Intelligent Surface; Physical-layer Security; fairness; User Equipment; Eavesdropping; Machine Learning; Reinforcement Learning; Deep Reinforcement Learning